ANALISIS PEMBENTUKAN TINGKAT KEPERCAYAAN KONSUMEN PADA USAHA PERCETAKAN DIGITAL “CV.ABC” - Ana Rusmardiana (JABE (Journal of Applied Business and Economic), 2015)
The level of consumer trust in a business interaction is a crucial prerequisite as the basis for the business person in the conduct of business transactions, as well as the opinion of some experts (Mentzer and Min,2000; Blumberg,2001; Spector and Jones, 2004) which in essence claimed business transactions would not have happened if a trust boundary of the verge is not achieved between the perpetrators of the  business. Given the importance of consumer trust in the provider, then it is important to know how the formation of consumer trust in the digital printing sector in Jakarta so that the service provider may be chosen by the consumer. Data obtained from the  22 (twenty-two) of the respondents who meet the criteria as a viable consumer by using interview techniques in subsequent semi-structured dept interviews in dept, later in the conversation transcript to be analyzed with reference to the operational variables.